1995
DOI: 10.2214/ajr.164.2.7839975
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of benign and malignant adnexal masses: relative value of gray-scale, color Doppler, and spectral Doppler sonography.

Abstract: OBJECTIVE.The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
56
0
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(71 citation statements)
references
References 15 publications
9
56
0
6
Order By: Relevance
“…Vascularity in cystic lesions was seen equally in septae as well as in wall, but in solid malignant tumors, the central vascularity was observed in 87.5 % cases and peripheral vascularity in 37.5 % cases. These findings were correlated well with the study by Valentin et al [8] and Kurjak et al [7], but the study by Sharon Stein et al [9] suggested that internal color flow cannot be used as a predictor of malignancy (PPV 49 %), but the absence of color flow suggested benignity (NPV 94 %).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Vascularity in cystic lesions was seen equally in septae as well as in wall, but in solid malignant tumors, the central vascularity was observed in 87.5 % cases and peripheral vascularity in 37.5 % cases. These findings were correlated well with the study by Valentin et al [8] and Kurjak et al [7], but the study by Sharon Stein et al [9] suggested that internal color flow cannot be used as a predictor of malignancy (PPV 49 %), but the absence of color flow suggested benignity (NPV 94 %).…”
Section: Resultssupporting
confidence: 91%
“…Extrapolating the data of the present study using the criterion PI \ 1.0 and \0.4 proposed by Kurjak et al [7] and Buy et al [11], 92.5 % of malignant tumors and 6.82 % of benign tumors showed PI \ 1.0, while only 20 % malignant tumors and 2.27 % of the benign tumors showed RI \ 0.4. As elucidated previously by many authors [12,13], the absence of vascularity is always indicative of benignity (Fig. 4).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…It also suggests that B-Mode USG is very accurate in diagnosing true negative patient among the women who have benign ovarian masses. Sharon M Stein et al, also reported high sensitivity (98%) and negative predictive value (99%) in their study [15].…”
Section: Methodsmentioning
confidence: 67%
“…Ultrasound morphology of various types of adnexal pathology is described in reference [74] and the diagnostic value of adding Doppler ultrasound to gray scale imaging is thoroughly discussed in reference [95]. The sensitivity and specificity of pattern recognition both with regard to malignancy and specific diagnoses are shown in Table 6 [94,[96][97][98][99][100][101][102][103][104][105][106][107][108][109]. A meta-analysis describing the diagnostic accuracy of transvaginal ultrasound specifically for the diagnosis of endometriomas has been published [110].…”
Section: Palpable Pelvic Massmentioning
confidence: 99%